(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to determine the effect of using ritual illustrations in the physical education lesson during and after explaining the skill of learning some basic skills for soccer halls for middle school students, as teaching units were established in this regard to teaching some of these skills, which are among the subjects of the Ministerial Curriculum, Gymnasium, for intermediate students. The second. The sample consisted of 60 male and female students from the second intermediate stage in Tariq Bin Ziyad School/Al-Rusafa First School/Baghdad Governorate. The sample was divided into two equal groups: one of them is experimental and its number is 30 students, and it was taught using pictures and videos in the physical education lesson during and after the explanation of the skill, and the other was a control, which is 30 students and this method is used to explain the skill without any pictures or films Illustrative. For the purposes of the study, some skill tests were used in gyms, and the results resulted in statistically significant differences in favor of the experimental group in the skill tests under study, which indicates the importance and effectiveness of using pictures and videos in the physical education lesson in learning football skills for the halls under investigation for students stage. Type of Paper——Review